Notary Responsibility in Making a Deed of Statement of Resolution of the GMS: Problems and Legal Consequences (Study of Decision No. 373/Pdt.G/2022/PN Jkt.Sel) - Safira Firda Ivena; Noor Saptanti; Erna Dyah Kusumawati (Jurnal Smart Hukum (JSH), 2026)
A notary is a public official who is responsible for the deeds they produce. A notarial deed, as an authentic deed, possesses perfect evidentiary power. An authentic deed drawn up by or before a notary must fulfill both formal and material requirements. If these requirements are not met, the deed may be declared legally defective, resulting in its nullification or invalidity. This study aims to analyze the legal responsibility of a notary and the legal consequences arising from the annulment of a notarial deed through a case approach based on Decision Number 373/Pdt.G/2022/PN Jkt.Sel. The results show that, in the decision, the notary was proven to have committed an unlawful act due to non-compliance with the provisions stipulated in the Law on Notary Position and the Notary Code of Ethics in drafting the Deed of Statement of Meeting Resolutions. Consequently, the deed was declared invalid and without legal force. The annulment gives rise to legal liability on the part of the notary and affects the validity of corporate decisions embodied in the deed, thereby creating legal implications for the parties concerned.